2021
DOI: 10.1111/1744-7917.12904
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of egg‐specific protein causes female sterility inBombyx mori

Abstract: Yolk proteins are the main source of nutrients during embryonic and early larval development in oviparous animals. Therefore, vitellogenesis is crucial for reproduction. The silkworm, Bombyx mori, is a model lepidopteran insect in which there are three yolk proteins: vitellin, 30-kDa protein, and egg-specific protein (Esp). In this study, we explored the gene function of Esp through transgenic clustered regularly interspaced palindromic repeats (CRISPR) / CRISPR-associated protein 9 technology-mediated mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Esp is a glycolipoprotein that is synthesized by follicular cells and completely exhausted during embryogenesis (Toshima & Kawasaki, 2002 ). Mutation of Esp leads to female sterility; the eggs of mutant females are smaller and lighter in color than those of wild‐type females and fail to hatch (Xu et al ., 2021 ). In our study, ablation of lncR26319 and EndoA or overexpression of miR‐2834 resulted in a reduction of EndoA and disruption of Vg/VgR endocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esp is a glycolipoprotein that is synthesized by follicular cells and completely exhausted during embryogenesis (Toshima & Kawasaki, 2002 ). Mutation of Esp leads to female sterility; the eggs of mutant females are smaller and lighter in color than those of wild‐type females and fail to hatch (Xu et al ., 2021 ). In our study, ablation of lncR26319 and EndoA or overexpression of miR‐2834 resulted in a reduction of EndoA and disruption of Vg/VgR endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…U6 was used as an internal control. The primers used are listed in Table 1, primers for yolk protein genes such as Vg, Esp, low molecular weight lipoprotein1-4 (Lp1-4), Lp6-7 of 30K protein family were as in Xu et al, RP49 was used as internal control (Xu et al, 2021). The 2 -Ct Ct method (Winer et al, 1999) was used to calculate the relative expression of mRNAs from the Cts obtained in the PCR quantification (Ct is the cycle threshold, which indicates the number of cycles experienced when the fluorescent signal in each reaction tube reaches a set threshold).…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr) T...mentioning
confidence: 99%
“…It suggests to us that they may be involved in reproduction. Although little is known about the biological role of SPs/SPHs involved in reproduction, deficiency of few SPs/SPHs can lead to abnormal development of reproductive system and severe influence of fertility (Laflamme & Wolfner, 2013; Liu et al, 2013; Xu, Wang, et al, 2020; Xu, Wang, et al, 2022). Downregulation of AsTryP gene of Adelphocoris suturalis inhibits ovarian development and female fertility (Huang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Some genes are deposited in eggs as a maternal factor to determine the dorsal‐ventral polarity of embryos (Cao et al, 2015). Egg‐specific SPs in B. mori have been recorded as primary proteins conferring oogenesis and fertility (Xu, Bi, et al, 2020; Xu, Wang, et al, 2022). Knockdown of the SP gene, Nl_PCE3 , influences the eggshell formation of eggs and ovulation in N. lugens (Wu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a considerable number of studies have showed serine proteases are specifically expressed in reproductive tissues in Bombyx mori (Cesari et al, 2010). For example, we have successfully characterized and functionally ovarian serine protein or egg specific protein, as primary proteins conferring the oogenesis and fertility in B. mori (Xu et al, 2020b(Xu et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%